Triple Intergenotype Recombination of Human Astrovirus 5, Human Astrovirus 8, and Human Astrovirus 1 in the Open Reading Frame 1a, Open Reading Frame 1b, and Open Reading Frame 2 Regions of the Human Astrovirus Genome - Hongyu Wei; Kattareeya Kumthip; Pattara Khamrin; Arpaporn Yodmeeklin; Nutthawadee Jampanil; Phitchakorn Phengma; Zhenfeng Xie; Nuthapong Ukarapol; Hiroshi Ushijima; Niwat Maneekarn (Microbiology Spectrum, 2023)
ABSTRACT Human astrovirus (HAstV) strains exhibit high levels of genetic diversity, and many recombinant strains with different recombination patterns have been reported. The aims of the present study were to investigate the emergence of HAstV recombinant strains and to characterize the recombination patterns of the strains detected in pediatric patients admitted to the hospital with acute gastroenteritis in Chiang Mai, Thailand. A total of 92 archival HAstV strains detected in 2011 to 2020 were characterized regarding their open reading frame 1a (ORF1a) genotypes in comparison with their ORF1b genotypes to identify recombinant strains. The recombination breakpoints of the putative recombinant strains were determined by whole-genome sequencing and were analyzed by SimPlot and RDP software. Three HAstV strains (CMH-N178-12, CMH-S059-15, and CMH-S062-15) were found to be recombinant strains of three different HAstV genotypes, i.e., HAstV5, HAstV8, and HAstV1 within the ORF1a, ORF1b, and ORF2 regions, respectively. The CMH-N178-12 strain displayed recombination breakpoints at nucleotide positions 2681 and 4357 of ORF1a and ORF1b, respectively, whereas the other two recombinant strains, CMH-S059-15 and CMH-S062-15, displayed recombination breakpoints at nucleotide positions 2612 and 4357 of ORF1a and ORF1b, respectively. This is the first study to reveal nearly full-length genome sequences of HAstV recombinant strains with a novel recombination pattern of ORF1a-ORF1b-ORF2 genotypes. This finding may be useful as a guideline for identifying other recombinant HAstV strains in other geographical regions and may provide a better understanding of their genetic diversity, as well as basic knowledge regarding virus evolution. IMPORTANCE Recombination is one of the mechanisms that plays a crucial role in the genetic diversity and evolution of HAstV. We wished to investigate the emergence of HAstV recombinant strains and to analyze the whole-genome sequences of the putative HAstV recombinant strains detected in pediatric patients with acute gastroenteritis in 2011 to 2020. We reported 3 novel intergenotype recombinant strains of HAstV5-HAstV8-HAstV1 at the ORF1a-ORF1b-ORF2 regions of the HAstV genome. The hot spots of recombination occur frequently near the ORF1a-ORF1b and ORF1b-ORF2 junctions of the HAstV genome. The findings indicate that intergenotype recombination of HAstV occurs frequently in nature. The emergence of a novel recombinant strain allows the new virus to adapt and successfully escape from the host immune system, eventually emerging as the predominant genotype to infect human populations that lack herd immunity against novel recombinant strains. The virus may cause an outbreak and needs to be monitored continually.